The Role of Trust As a Mediating The Influence of Reverse Logistics on Customer Satisfaction at Shopee Indonesia - Mawadi, Citra Putri; Sitanggang, Nadia Veronica; Olfebri, Olfebri; Saidah, Deslida (Institut Transportasi dan Logistik Trisakti, 2023)
This study aims to determine the role of trust in mediating the influence of reverse logistics on customer satisfaction at Shopee Indonesia. The analysis technique used in this study is a descriptive research of quantitative analysis with data analysis techniques using Path Analysis. Data collection was carried out by distributing questionnaires through google forms to 100 respondents. Data testing includes validity tests, reliability tests and path analysis. The results showed that reverse logistics analysis has a significant influence on customer satisfaction. However, trust has not mediated significantly between the effect of reverse logistics on customer satisfaction